Dynamic changes of gap junctions and cytoskeleton during in vitro culture of cattle oocyte cumulus complexes - Sutovský, P; Fléchon, J E; Fléchon, B; Motlik, J; Peynot, N; Chesné, P; Heyman, Y (Biology of reproduction, 1993)
Changes in cell-to-cell contact and distribution of cytoskeletal components were investigated during in vitro culture of cattle oocyte cumulus complexes (OCC). Freeze-fracture analysis (FF), microinjections of the fluorescent dye Lucifer Yellow (LY), immunofluorescence, and ultrastructural immunocytochemistry were used. The cumulus cells (CC) remained in close contact via gap junctions (GJ) constituted of connexin43 (Cx43) during the entire culture time. Whereas the GJ decreased in diameter after 24 h of culture, their number was still substantially great at that time. The Cx43-positive GJ, localized between corona radiata cell projections and oolemma, disappeared after 6 h of culture. Concomitantly, the OCC lost the ability to transfer LY from cumulus to oocyte, and connexin32 (Cx32) became detectable in the oocytes. Both the changes in corona-oocyte coupling and cumulus expansion were preceded by the redistribution of F-actin in cytoplasm of CC. These data indicate that functional GJ linked the CC until the second meiotic arrest. However, the removal of Cx43-positive GJ interconnecting cytoplasmic projections of corona radiata cells with the oocyte was temporally correlated with germinal vesicle breakdown. The present results suggest the pivotal role of the cytoskeleton (F-actin) in cumulus expansion.
Keywords: fluorescenční protilátková technika; Intermediate Filaments; Isoquinolines; cytoskelet; Actin Cytoskeleton; Connexin 43; Microscopy, Electron; mikrofilamenta; konexin 43; aktiny; Intercellular Junctions; Female; Tubulin; Microtubules; intermediární filamenta; zvířata; Freeze Fracturing; Immunohistochemistry; Vimentin; imunohistochemie; mikrotubuly; časové faktory; oocyty; fluorescenční barviva; Cattle; ženské pohlaví; Fluorescent Dyes; tubulin; skot; Actins; Fluorescent Antibody Technique; elektronová mikroskopie; Animals; mrazové lámání; mezibuněčné spoje; Oocytes; Time Factors; Cytoskeleton; isochinoliny; vimentin